PENGARUH PROSES PENGADUKAN TANAH LIAT TERHADAP KUAT TEKAN BATA MERAH - Yovanda Putra Medika; Elhusna Elhusna; Ade Sri Wahyuni (Universitas Bengkulu, 2019)
One of the conventional brick production processes is the clay stirring process, which the red brick clay mortar mix is, done by stepping on it. This research is aimed to know the duration of stepping on the process of the clay mortar mixing to the red brick properties. The method of this research is experimental. The brick making process is done in the way that the factory does. The variation of stepping on brick dough is about 20, 25, 30, 32, 35 and 40 minutes where 32minutes is factory time. The objects of the test created on this research is 15 for normal bricks and 90 for variation bricks. The testing of the compressive strength of the brick refers to SNI 03-416-1996 and uses the Compression Machine Hand Operated with capacity 250 kN. The biggest of of the compressive strength of the brick is on stepping on brick dough in 40 minutes with 1,09 MPa. This research shows that the length of the stirring process determines the strength of the produced bricks; simply put, the longer the stirring process gets, the stronger bricks become.